Multilateralidad en América Latina y el Caribe y el genocidio en Gaza - Jaramillo Jassir, Mauricio (El Colegio de México A.C., 2024)
The region of Latin America and the Caribbean has sought prominence since the beginning of the crisis between Israel and Palestine, as many of its states have aimed for a balance in their relations with both parties. With few exceptions, almost all states today have diplomatic relations with the Palestinian National Authority (PNA), recognizing it as a state entity (except for Paraguay), and several have recently attempted to play a more active role in the Middle East. Given the dramatic situation at the end of 2023 in that region, Latin America once again reaffirmed international law as the guiding principle for its actions. Consequently, several states decided to undertake actions within the framework of multilateralism to express solidarity with Palestine and demand a ceasefire in Gaza, and an end to subsequent violence in other occupied territories. While Latin America may be weakened in its multilateral spaces, its express and permanent desire for the defense of international law, international humanitarian law, and the United Nations system remains, or rather, what is left of them.